Babaji life and teachings of Farid-ud-Din Ganj-i Shakar - Čaġatāʾī, Muḥammad Ikrām (Lahore Sang-e- Meel Publ., 2006)
Saikh Farid-uddin, 1175?-1265, Panjabi Sufi poet
Includes index. - Includes bibliographical references (p. [617]-618)
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Farid Uddin 1175?-1265; Sufis -- Biography -- Pakistan; Sufism -- Pakistan; Aufsatzsammlung